A method for improving poly inter-poly crystalline silicon film thickness of a topcon cell
Patent Information
- Application Number
- CN202411556439.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-11-01
AI Technical Summary
[0006]本发明的目的是提供一种用于改善TOPcon电池poly片间多晶硅膜膜厚的方法,解决LP单插生产变更为双插工艺生产会带来poly片间膜厚均匀性变差的问题
1、本发明优化预处理步骤,预处理的对象不包括石英舟托,因为石英舟托会吸收部分硅烷沉积表面,导致饱和清洗舟托及小舟情况下所需硅烷量要远大于只洗小舟的饱和量,不洗舟托可有效减少硅烷耗量,降低了生产成本。
Smart Images

Figure CN119630093B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of silicon solar cells and relates to a method for improving the thickness of the polycrystalline silicon film between poly wafers in TOPcon solar cells. Background Technology
[0002] TOPCon technology, short for tunneling oxide passivation contact technology, is an advanced process technology with significant advantages in photovoltaic cell manufacturing. Its core concept lies in effectively reducing the recombination of conjugate pairs by separating hole-electron conjugate pairs, thereby significantly improving the power generation performance of photovoltaic cells. This technology is based on the principle of selective carriers, achieved by carefully preparing an ultrathin layer of silicon oxide on the back of the cell and depositing a thin layer of doped silicon on top of it; together, they form a highly efficient passivation contact structure.
[0003] This passivated contact structure plays a crucial role in photovoltaic cells. It not only significantly reduces the recombination rate on the cell surface but also effectively minimizes recombination at metal contacts, opening up vast possibilities for further improvements in cell conversion efficiency. Therefore, TOPCon technology, upon its introduction, was rapidly adopted in the photovoltaic cell manufacturing field and has become one of the mainstream photovoltaic cell technologies.
[0004] With the continuous development and improvement of TOPCon process technology, its core process, LPCVD (Low-Pressure Chemical Vapor Deposition), has also made significant progress. To meet higher output demands, the LPCVD process has undergone in-depth development, evolving from the original single-intercalation process to a dual-intercalation process. This change means that in the original quartz boat, the number of wafers has increased from one in one tank to two in one tank, thereby greatly improving production capacity.
[0005] However, the shift from single-intercalation (LP) to dual-intercalation production also presents some challenges. In particular, the uniformity of poly film thickness between poly wafers may deteriorate under dual-intercalation. This issue becomes especially pronounced after the new ark wafers reach saturation, as they may require a period of time to reach optimal saturation, during which time the poly film thickness may be relatively thin. Therefore, ensuring uniform poly film thickness between poly wafers while maintaining increased production capacity has become one of the key challenges for the further development of TOPCon process technology. Summary of the Invention
[0006] The purpose of this invention is to provide a method for improving the thickness of polycrystalline silicon films between poly wafers in TOPcon solar cells, thereby solving the problem of poor uniformity of poly film thickness between wafers caused by changing from LP single-intercalation production to double-intercalation production.
[0007] The technical solution adopted in this invention is a method for improving the thickness of the polycrystalline silicon film between poly wafers in TOPcon solar cells, comprising the following steps: Step 1: Pre-process the quartz boat. The object of pre-processing does not include the quartz boat holder. Step 2: Check the airtightness of the furnace tubes; Step 3: Wafer loading and boat loading. Load the silicon wafers into the quartz boat, transport the quartz boat into the furnace tube, heat the furnace tube and keep it at 600~700℃ for 500~700s, while purging with nitrogen gas for 3~5min. Step 4: Evacuate the furnace tube after the treatment in Step 3 for 2-3 minutes until the pressure is low, and keep the temperature constant at 550-600℃. Step 5: Constant pressure ventilation. A certain amount of silane is pre-introduced into the furnace tube after the treatment in Step 4 to make the furnace tube pressure rise and maintain constant pressure, and the temperature is kept constant at 550~600℃. Step 6: Multilayer deposition process. First, silane is introduced at high temperature, and the silane thermally decomposes into the first layer of elemental silicon, which is deposited on the surface of the passivation layer. Second, silane is introduced at high temperature, and the silane thermally decomposes into the second layer of elemental silicon, which is deposited on the surface of the passivation layer. Third, silane is introduced at high temperature, and the silane thermally decomposes into the third layer of elemental silicon, which is deposited on the surface of the passivation layer. Step 7: After the multilayer deposition process is completed, the unreacted gases and some products are extracted from the furnace tube using a vacuum pump. Step 8: Back pressure, nitrogen gas is introduced into the furnace tube to bring the pressure back to atmospheric pressure, in preparation for unloading the boat; Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
[0008] The invention is further characterized by: Furthermore, the preprocessing includes the following steps: The quartz boat was treated with an alkaline solution for alkaline washing. The quartz boat after alkali washing is then washed with water. The quartz boat was acid-washed using a mixed acid solution; The acid-washed quartz boat is then washed with water. The quartz boat, after being washed, is slowly lifted and dehydrated. The dehydrated quartz boat is then dried.
[0009] Furthermore, the alkaline solution is a mixed solution of NaOH and H2O2, wherein NaOH accounts for 2.5-4.0% of the volume fraction of the mixed solution, and H2O2 accounts for 3.5-6.0% of the volume fraction of the mixed solution.
[0010] Furthermore, the mixed acid solution comprises, by mass percentage, the following components: 0.3–1.5% hydrogen chloride, 0.1–0.2% hydrogen fluoride, 0.05–0.4% oxidant, 0.05–0.1% complexing agent, 0.02–0.05% surfactant, with the balance being water.
[0011] Furthermore, the oxidant is selected from any one or a combination of at least two of hydrogen peroxide, peracetic acid, or ammonium persulfate; The complexing agent is any one or a combination of at least two of ethylenediaminetetraacetic acid, hydroxyethyliminodiacetic acid, and hydroxyethylethylenediaminetriacetic acid; The surfactant is any one or a combination of at least two of palmitic acid, polyethylene glycol, or fatty alcohol polyoxyethylene ether.
[0012] Furthermore, the alkaline washing treatment is carried out according to the following steps: First, the quartz boat is immersed in the alkaline solution and then ultrasonically rinsed. The temperature for static soaking is 15-35℃, and the soaking time is 30-50 minutes; The ultrasonic rinsing temperature is 30-40℃, the ultrasonic rinsing frequency is 30-40kHz, and the ultrasonic rinsing time is 45-60min. The pickling process is carried out according to the following steps: First, the quartz boat is immersed in the mixed acid solution and then ultrasonically rinsed. The temperature for static soaking is 15-35℃, and the soaking time is 30-50 minutes; The ultrasonic rinsing temperature is 30-40℃, the ultrasonic rinsing frequency is 30-40kHz, and the ultrasonic rinsing time is 45-60min. The specific steps of the water washing treatment are as follows: First, soak the quartz boat that has been acid-washed or alkali-washed in pure water, and then rinse it with spray. The temperature for static soaking is 10-20℃, and the soaking time is 20-40 minutes; The temperature of the spray rinsing is 10–20℃, and the flow rate is 5–15 m³ / h. 3 / h, the spray rinsing time is 30-60min.
[0013] Furthermore, in step 5, the constant pressure is maintained at 150 mbar.
[0014] Furthermore, the vacuuming conditions in step 7 are set to a temperature of 550~600℃ and a time of 1~3 minutes.
[0015] Furthermore, the back pressure conditions in step 8 are set as follows: temperature 550~600℃, nitrogen flow rate 10000~30000sccm, and time 1~3min.
[0016] Furthermore, the parameters for the first deposition in step 6 are set as follows: temperature 500~650℃, silane flow rate 200~650sccm, and time 45~60min; The parameters for the second deposition were set as follows: temperature 500-650℃, silane flow rate 200-650 sccm, and time 30-45 min. The parameters for the third deposition were set as follows: temperature 500-650℃, silane flow rate 200-650 sccm, and time 35-40 min.
[0017] The beneficial effects of this invention are as follows: 1. The present invention optimizes the pretreatment steps. The object of pretreatment does not include the quartz boat tray, because the quartz boat tray will absorb some of the silane deposits on the surface. As a result, the amount of silane required for saturated cleaning of the boat tray and the small boat is much greater than the saturated amount required for cleaning only the small boat. Not cleaning the boat tray can effectively reduce silane consumption and reduce production costs.
[0018] 2. This invention changes the traditional two-step deposition process to a three-step deposition process, which can more precisely control the thickness, composition and structure of the tunneling oxide layer and passivation layer, improve the open-circuit voltage and short-circuit current of the battery, and thus improve the photoelectric conversion efficiency. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a schematic diagram of the process of the present invention. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.
[0022] The following is in conjunction with the appendix Figure 1 The invention will be described in detail with specific embodiments: A method for improving the thickness of polycrystalline silicon films between poly wafers in TOPCon solar cells includes the following steps: Step 1: Pre-treat the quartz boat. The pre-treatment does not include the quartz boat holder, because the quartz boat holder will absorb some of the silane deposited on the surface. This means that the amount of silane required for saturated cleaning of the boat holder and the small boat is much greater than the saturated amount required for cleaning only the small boat. Not cleaning the boat holder can effectively reduce silane consumption and effectively improve the problem of thin film thickness on the first boat when a new boat is put into production.
[0023] Step 2: The reaction needs to be completed under vacuum conditions. The airtightness of the furnace tube is checked to ensure that the leakage rate meets the requirements of the process and to prevent air from entering. Step 3: Wafer loading and boat loading. The silicon wafer is loaded into the quartz boat and transported to the furnace tube. The furnace tube is heated and kept at 600~700℃ for 500~700s. At the same time, nitrogen gas is introduced to purge for 3~5 minutes. The nitrogen gas removes the air and moisture in the cavity to prevent air or moisture from contaminating the silicon wafer and causing dirt to appear on the coating.
[0024] Step 4: Evacuate the furnace tube after Step 3 for 2-3 minutes until the pressure is low enough to meet the vacuum conditions required for the thin film deposition reaction, and keep the temperature constant at 550-600℃. Step 5: Constant pressure ventilation. Before depositing the thin film, a certain amount of silane is pre-introduced into the furnace tube after the treatment in step 4 so that the furnace tube reaches the pressure atmosphere required by the process in advance. The pressure of the furnace tube rises and is maintained at constant pressure. Under constant pressure conditions, the temperature is kept constant at 550~600℃. Step 6: Multilayer deposition process. First, silane is introduced at high temperature, and the silane thermally decomposes into the first layer of elemental silicon, which is deposited on the surface of the passivation layer. Then, silane is introduced at high temperature a second time, and the silane thermally decomposes into the second layer of elemental silicon, which is deposited on the surface of the passivation layer. Third, silane is introduced at high temperature a third time, and the silane thermally decomposes into the third layer of elemental silicon, which is deposited on the surface of the passivation layer. The parameters for the first deposition in step 6 are set as follows: temperature 500~650℃, silane flow rate 200~650sccm, and time 45~60min. The parameters for the second deposition were set as follows: temperature 500-650℃, silane flow rate 200-650 sccm, and time 30-45 min. The parameters for the third deposition were set as follows: temperature 500-650℃, silane flow rate 200-650 sccm, and time 35-40 min.
[0025] Step 7: After the multilayer deposition process is completed, the unreacted gas and some products are extracted from the furnace tube by a vacuum pump. The vacuum conditions in step 7 are set at a temperature of 550~600℃ and a time of 1~3min. Step 8: Backpressure. Nitrogen gas is introduced into the furnace tube to bring the pressure back to atmospheric pressure, preparing for opening the furnace door. The backpressure conditions for step 8 are set as follows: temperature 550~600℃, nitrogen flow rate 10000~30000sccm, and time 1~3min.
[0026] Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
[0027] Preprocessing includes the following steps: The quartz boat was treated with an alkaline solution for alkaline washing. The quartz boat after alkali washing is then washed with water. The quartz boat was acid-washed using a mixed acid solution; The acid-washed quartz boat is then washed with water. The quartz boat, after being washed, is slowly lifted and dehydrated; The dehydrated quartz boat is then dried.
[0028] The alkaline solution is a mixture of NaOH and H₂O₂, with NaOH accounting for 2.5–4.0% of the volume and H₂O₂ accounting for 3.5–6.0% of the volume. In the mixed solution, NaOH can effectively decompose and remove grease, organic matter, and other contaminants from the surface of the quartz boat, while H₂O₂ can further oxidize and decompose the contaminants on the surface of the quartz boat, thus improving the cleaning effect.
[0029] Alkaline solutions ensure effective cleaning while avoiding excessive corrosion and damage to the quartz boat. The cleaned quartz boat exhibits a high degree of surface smoothness, which contributes to improved performance and lifespan during use. The cleaning effect of a mixture of NaOH and hydrogen peroxide ensures that the surface smoothness of the quartz boat meets the required standards.
[0030] The mixed acid solution comprises the following components by mass percentage: 0.3–1.5% hydrogen chloride, 0.1–0.2% hydrogen fluoride, 0.05–0.4% oxidant, 0.05–0.1% complexing agent, 0.02–0.05% surfactant, and the balance being water.
[0031] The oxidizing agent in the mixed acid solution can further oxidize and decompose organic matter and other stubborn contaminants on the surface of the quartz boat. By enhancing the cleaning effect, the oxidizing agent helps reduce mechanical friction and damage to the quartz boat.
[0032] Complexing agents can form stable complexes with metal ions, thereby reducing the residue of metal ions on the surface of the quartz boat. This helps prevent metal ion contamination and corrosion of the quartz boat.
[0033] Surfactants reduce the surface tension of cleaning solutions, making them easier to penetrate the tiny crevices and depressions on the surface of the quartz boat. This helps improve cleaning effectiveness and reduces damage to the quartz boat during the cleaning process.
[0034] The components in a mixed acid solution can work synergistically at appropriate concentrations, improving cleaning effectiveness while reducing environmental pollution. This helps reduce wastewater treatment costs and negative environmental impacts during the cleaning process.
[0035] The oxidant is selected from any one or a combination of at least two of hydrogen peroxide, peracetic acid, or ammonium persulfate. All of these oxidants possess strong oxidizing properties and can effectively remove organic matter, metallic impurities, and other contaminants from the surface of the quartz boat. Specifically, hydrogen peroxide and peracetic acid release nascent oxygen upon contact with organic matter, thus oxidizing and decomposing the contaminants. Ammonium persulfate also has strong oxidizing properties, rapidly decomposing to produce sulfate ions and free radicals, which further react with the contaminants.
[0036] Combining these oxidants can work synergistically to improve cleaning efficiency. Different oxidants may have different removal effects on different types of contaminants, so using them in combination can ensure more comprehensive removal of contaminants from the surface of the quartz boat.
[0037] The aforementioned oxidants typically decompose to produce only oxygen, water, or other harmless substances, leaving no harmful residues after use. This is crucial for the manufacturing process of TOPCon batteries, as any harmful residues can affect the battery's performance and efficiency.
[0038] The complexing agent is any one or a combination of at least two of ethylenediaminetetraacetic acid, hydroxyethyliminodiacetic acid, and hydroxyethylethylenediaminetriacetic acid.
[0039] Using any one or a combination of at least two of ethylenediaminetetraacetic acid (EDTA), hydroxyethyliminodiacetic acid, or hydroxyethylethylenediaminetriacetic acid as a complexing agent to clean the quartz boats used in TOPCon can bring the following beneficial effects: The aforementioned complexing agent can form stable complexes with metal ions (such as iron, copper, and nickel) on the surface of the quartz boat, thereby effectively removing these metal ions. This complexing effect prevents metal ions from depositing on the surface of the quartz boat, avoiding interference with subsequent processes.
[0040] By using a complexing agent to complex with metal ions, metal ions on the surface of a quartz boat can be rapidly removed, improving cleaning efficiency. This is crucial for the manufacturing process of TOPCon batteries, as the presence of metal ions can affect battery performance and efficiency.
[0041] Compared to traditional mechanical cleaning methods, cleaning with complexing agents reduces mechanical damage to the quartz boat surface. The complexing agent can penetrate into the tiny crevices and depressions on the quartz boat surface, forming complexes with metal ions and removing them without damaging the surface structure. By removing metal ions and other contaminants from the quartz boat surface, its performance remains stable. This is crucial for ensuring the quality and reliability of TOPCon batteries.
[0042] Complexing agents form stable complexes with metal ions during the cleaning process, thereby reducing the toxicity of the cleaning wastewater. This helps reduce costs and environmental risks associated with wastewater treatment. Compared to wastewater containing heavy metal ions, wastewater containing complexes is easier to treat and dispose of. This helps reduce wastewater treatment costs and minimize environmental pollution.
[0043] The surfactant is any one or a combination of at least two of palmitic acid, polyethylene glycol, or fatty alcohol polyoxyethylene ether.
[0044] Surfactants significantly reduce the surface tension of water, allowing it to better penetrate the tiny crevices and depressions on the surface of a quartz boat, thus more effectively removing surface dirt and contaminants. Surfactants penetrate the dirt on the surface of the quartz boat and remove it through chemical reactions or physical processes without damaging the surface structure of the quartz boat.
[0045] By removing dirt and contaminants from the surface of the quartz boat, its smoothness and cleanliness can be maintained, thus ensuring stable performance. This is crucial for the manufacturing process of TOPCon batteries, as the performance of the quartz boat directly affects the quality and efficiency of the battery.
[0046] Alkaline washing treatment shall be carried out according to the following steps: First, the quartz boat is immersed in the alkaline solution and then ultrasonically rinsed. The temperature for static soaking is 15-35℃, and the soaking time is 30-50 minutes; The ultrasonic rinsing temperature is 30-40℃, the ultrasonic rinsing frequency is 30-40kHz, and the ultrasonic rinsing time is 45-60min.
[0047] The quartz boat surface becomes cleaner and smoother after alkaline washing, providing a good foundation for subsequent battery manufacturing processes. A clean quartz boat ensures process stability and product quality during battery manufacturing, thereby improving battery conversion efficiency and lifespan.
[0048] Pickling is carried out according to the following steps: First, the quartz boat is immersed in the mixed acid solution and then ultrasonically rinsed. The temperature for static soaking is 15-35℃, and the soaking time is 30-50 minutes; The ultrasonic rinsing temperature is 30-40℃, the ultrasonic rinsing frequency is 30-40kHz, and the ultrasonic rinsing time is 45-60min.
[0049] Pickling can effectively remove oxides, nitrides, or other impurities, including removing silicon oxide and silicon nitride films from the silicon wafer surface, ensuring the cleanliness of the silicon wafer surface and providing high-quality silicon wafers for subsequent process steps.
[0050] The specific steps of the water washing process are as follows: First, soak the quartz boat that has been acid-washed or alkali-washed in pure water, and then rinse it with spray. The temperature for static soaking is 10-20℃, and the soaking time is 20-40 minutes; The temperature of the spray rinsing is 10-20℃, and the flow rate is 5-15m³ / h. 3 / h, the spray rinsing time is 30-60min.
[0051] The main purpose of water washing is to remove residual mixed acid or alkaline solutions from the surface of the silicon wafer, as well as other impurities that may be present on the surface of the quartz boat.
[0052] Pretreatment processes such as alkaline washing, acid washing, and water washing can also be carried out using tank cleaning operations. Tank cleaning can process multiple quartz boats simultaneously, greatly improving cleaning efficiency.
[0053] Example 1 Step 1: Pre-treat the quartz boat by using an alkaline solution to wash it. First, soak the quartz boat in the alkaline solution and then ultrasonically rinse it. The temperature for standing soaking is 35℃, and the soaking time is 50 minutes. The ultrasonic rinsing temperature was 40℃, the ultrasonic rinsing frequency was 40kHz, and the ultrasonic rinsing time was 60min.
[0054] The alkaline solution contains 2.8% NaOH and 5.0% H2O2 by volume in the mixed solution.
[0055] The quartz boat after alkali washing is then washed with water. First, the quartz boat after alkali washing is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 20℃, and the soaking time is 35 minutes. The temperature of the spray rinsing is 105℃, and the flow rate of the spray rinsing is 14m³ / h. 3 / h, the spray rinsing time is 30min.
[0056] The quartz boat was acid-washed using a mixed acid solution. First, the quartz boat was soaked in the mixed acid solution and then ultrasonically rinsed. The temperature for standing soaking is 35℃, and the soaking time is 50 minutes. The ultrasonic rinsing temperature was 40℃, the ultrasonic rinsing frequency was 40kHz, and the ultrasonic rinsing time was 60min.
[0057] The mixed acid solution contains, by mass percentage, 0.3% hydrogen chloride, 0.1% hydrogen fluoride, 0.05% oxidant, 0.05% complexing agent, and 0.05% surfactant, with the balance being water. The oxidant is a combination of hydrogen peroxide and ammonium persulfate; the complexing agent is ethylenediaminetetraacetic acid; and the surfactant is a combination of polyethylene glycol and fatty alcohol polyoxyethylene ether.
[0058] The quartz boat after acid pickling is washed with water. First, the acid-pickled quartz boat is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 14℃, and the soaking time is 30 minutes. The temperature of the spray rinsing is 18℃, and the flow rate of the spray rinsing is 10m³ / h. 3 / h, the spray rinsing time is 40min.
[0059] The quartz boat, after being washed, is slowly lifted and dehydrated; The dehydrated quartz boat is then dried.
[0060] Step 2: Check the airtightness of the furnace tubes; Step 3: Load the wafers and place them in the boat. Heat the furnace tube and keep it at 600℃ for 500 seconds. At the same time, purge with nitrogen gas for 3 minutes. Step 4: Evacuate the vacuum for 2 minutes until the pressure is low, and keep the temperature constant at 550℃. Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 550℃; Step 6: First, introduce silane at a high temperature of 500℃, with a silane flow rate of 200 sccm and a time of 45 min; then, introduce silane at a high temperature for the second time, with a temperature of 500℃, a silane flow rate of 200 sccm and a time of 30 min; finally, introduce silane at a high temperature for the third time, with a temperature of 500℃, a silane flow rate of 200 sccm and a time of 35 min.
[0061] After steps 7 and 6 are completed, a vacuum is drawn. The vacuum conditions are set at a temperature of 550℃ for 1 minute. Step 8: Back pressure. The back pressure conditions are set as follows: temperature 550~600℃, nitrogen flow rate 10000sccm, and time 1min.
[0062] Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
[0063] To verify the beneficial effects of the present invention, the product of Example 1 was selected for a control group experiment.
[0064] The control group experiment was conducted according to the following steps: Step 1: Pre-treat the quartz boat and boat support. Use an alkaline solution to perform alkaline washing on the quartz boat. First, soak the quartz boat in the alkaline solution and then perform ultrasonic rinsing. The temperature for standing soaking is 35℃, and the soaking time is 50 minutes. The ultrasonic rinsing temperature was 40℃, the ultrasonic rinsing frequency was 40kHz, and the ultrasonic rinsing time was 60min.
[0065] The alkaline solution contains 2.8% NaOH and 5.0% H2O2 by volume in the mixed solution.
[0066] The quartz boat after alkali washing is then washed with water. First, the quartz boat after alkali washing is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 20℃, and the soaking time is 35 minutes. The temperature of the spray rinsing is 105℃, and the flow rate of the spray rinsing is 14m³ / h. 3 / h, the spray rinsing time is 30min.
[0067] The quartz boat was acid-washed using a mixed acid solution. First, the quartz boat was soaked in the mixed acid solution and then ultrasonically rinsed. The temperature for standing soaking is 35℃, and the soaking time is 50 minutes. The ultrasonic rinsing temperature was 40℃, the ultrasonic rinsing frequency was 40kHz, and the ultrasonic rinsing time was 60min.
[0068] The mixed acid solution contains, by mass percentage, 0.3% hydrogen chloride, 0.1% hydrogen fluoride, 0.05% oxidant, 0.05% complexing agent, and 0.05% surfactant, with the balance being water. The oxidant is a combination of hydrogen peroxide and ammonium persulfate; the complexing agent is ethylenediaminetetraacetic acid; and the surfactant is a combination of polyethylene glycol and fatty alcohol polyoxyethylene ether.
[0069] The quartz boat after acid pickling is washed with water. First, the acid-pickled quartz boat is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 14℃, and the soaking time is 30 minutes. The temperature of the spray rinsing is 18℃, and the flow rate of the spray rinsing is 10m³ / h. 3 / h, the spray rinsing time is 40min.
[0070] The quartz boat, after being washed, is slowly lifted and dehydrated; The dehydrated quartz boat is then dried.
[0071] Step 2: Check the airtightness of the furnace tubes; Step 3: Load the wafers and place them in the boat. Heat the furnace tube and keep it at 600℃ for 500 seconds. At the same time, purge with nitrogen gas for 3 minutes. Step 4: Evacuate the vacuum for 2 minutes until the pressure is low, and keep the temperature constant at 550℃. Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 550℃; Step 6: First, introduce silane at a high temperature of 500℃, with a silane flow rate of 200 sccm and a time of 45 min; then, introduce silane at a high temperature for the second time, with a temperature of 500℃, a silane flow rate of 200 sccm and a time of 30 min; finally, introduce silane at a high temperature for the third time, with a temperature of 500℃, a silane flow rate of 200 sccm and a time of 35 min.
[0072] After steps 7 and 6 are completed, a vacuum is drawn. The vacuum conditions are set at a temperature of 550℃ for 1 minute. Step 8: Back pressure. The back pressure conditions are set as follows: temperature 550~600℃, nitrogen flow rate 10000sccm, and time 1min.
[0073] Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
[0074] Sample collection method: Parameter analysis was performed on the solar cells sintered in the same furnace within a single boat support. First, the 10 quartz boats in the same support were numbered sequentially from 1 to 10. Then, the quartz boats were divided into upper, middle, and lower regions. Solar cells were selected from quartz boats numbered 1, 3, 5, 7, and 9. Specifically, one solar cell was selected from each of the upper, middle, and lower regions of each quartz boat. The polyfilm thickness data of the selected sample's central region, upper left corner region, upper right corner region, lower left corner region, and lower right corner region were measured.
[0075] Table 1. Control Experiment Data The purpose of the first group of experiments was to verify the effect of cleaning the boat support versus not cleaning it on the inter-sheet thickness of the poly film. Table 1 shows that the film thickness compliance rate in the experimental group was 100%, while the compliance rate in the control group was 61%. Clearly, the compliance rate in the experimental group was significantly higher than that in the control group. Therefore, it can be concluded that not cleaning the boat support effectively improves the problem of thin poly film thickness.
[0076] Example 2 Step 1: Pre-treat the quartz boat by using an alkaline solution to wash it. First, soak the quartz boat in the alkaline solution and then ultrasonically rinse it. The temperature for standing soaking is 15℃, and the soaking time is 30 minutes; The ultrasonic rinsing temperature was 30℃, the ultrasonic rinsing frequency was 30kHz, and the ultrasonic rinsing time was 45min.
[0077] The alkaline solution contains 2.5% NaOH and 6.0% H2O2 by volume in the mixed solution.
[0078] The quartz boat after alkali washing is then washed with water. First, the quartz boat after alkali washing is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 13℃, and the soaking time is 26 minutes; The temperature of the spray rinsing is 12℃, and the flow rate of the spray rinsing is 8m³ / h. 3 / h, the spray rinsing time is 30min.
[0079] The quartz boat was acid-washed using a mixed acid solution. First, the quartz boat was soaked in the mixed acid solution and then ultrasonically rinsed. The temperature for static soaking is 15℃, and the soaking time is 45 minutes. The ultrasonic rinsing temperature was 32℃, the ultrasonic rinsing frequency was 34kHz, and the ultrasonic rinsing time was 46min.
[0080] The mixed acid solution contains 1% hydrogen chloride, 0.15% hydrogen fluoride, 0.2% oxidant, 0.07% complexing agent, and 0.03% surfactant, with the balance being water. The oxidant is hydrogen peroxide; the complexing agent is hydroxyethylethylenediaminetriacetic acid; and the surfactant is polyethylene glycol.
[0081] The quartz boat after acid pickling is washed with water. First, the acid-pickled quartz boat is soaked in pure water and then rinsed by spraying. The temperature for static soaking was 19℃, and the soaking time was 26 minutes. The temperature of the spray rinsing is 17℃, and the flow rate of the spray rinsing is 13m³ / h. 3 / h, the spray rinsing time is 35min.
[0082] The quartz boat, after being washed, is slowly lifted and dehydrated; The dehydrated quartz boat is then dried.
[0083] Step 2: Check the airtightness of the furnace tubes; Step 3: Load the wafers and place them in the boat. Heat the furnace tube and keep it at 700℃ for 700 seconds. At the same time, purge with nitrogen gas for 5 minutes. Step 4: Evacuate the vacuum for 2 minutes until the pressure is low, and keep the temperature constant at 550℃. Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 550℃; Step 6: First, introduce silane at a high temperature of 610℃, with a silane flow rate of 450 sccm and a time of 47 min; then, introduce silane at a high temperature of 620℃, with a silane flow rate of 550 sccm and a time of 42 min; finally, introduce silane at a high temperature of 630℃, with a silane flow rate of 350 sccm and a time of 39 min.
[0084] After steps 7 and 6 are completed, a vacuum is drawn. The vacuum conditions are set at a temperature of 574℃ for 1 to 3 minutes. Step 8: Back pressure. The back pressure conditions are set at a temperature of 568℃, a nitrogen flow rate of 20000 sccm, and a time of 2 minutes.
[0085] Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
[0086] Example 3 Step 1: Pre-treat the quartz boat by using an alkaline solution to wash it. First, soak the quartz boat in the alkaline solution and then ultrasonically rinse it. The temperature for static soaking is 18℃, and the soaking time is 36 minutes. The ultrasonic rinsing temperature was 33℃, the ultrasonic rinsing frequency was 32kHz, and the ultrasonic rinsing time was 47min.
[0087] The alkaline solution contains 4.0% NaOH and 3.5% H2O2 by volume in the mixed solution.
[0088] The quartz boat after alkali washing is then washed with water. First, the quartz boat after alkali washing is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 11℃, and the soaking time is 24 minutes. The temperature of the spray rinsing is 13℃, and the flow rate of the spray rinsing is 7m³ / h. 3 / h, the spray rinsing time is 42min.
[0089] The quartz boat was acid-washed using a mixed acid solution. First, the quartz boat was soaked in the mixed acid solution and then ultrasonically rinsed. The temperature for static soaking was 18℃, and the soaking time was 41 minutes. The ultrasonic rinsing temperature was 34℃, the ultrasonic rinsing frequency was 38kHz, and the ultrasonic rinsing time was 47min.
[0090] The mixed acid solution contains, by mass percentage, 0.8% hydrogen chloride, 0.18% hydrogen fluoride, 0.22% oxidant, 0.06% complexing agent, and 0.04% surfactant, with the balance being water. The oxidant is a combination of peracetic acid and ammonium persulfate; the complexing agent is a combination of ethylenediaminetetraacetic acid and hydroxyethylethylenediaminetriacetic acid; and the surfactant is a combination of palmitoleic acid, polyethylene glycol, and fatty alcohol polyoxyethylene ether.
[0091] The quartz boat after acid pickling is washed with water. First, the acid-pickled quartz boat is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 12℃, and the soaking time is 28 minutes; The temperature of the spray rinsing is 13℃, and the flow rate of the spray rinsing is 7m³ / h. 3 / h, the spray rinsing time is 44min.
[0092] The quartz boat, after being washed, is slowly lifted and dehydrated. The dehydrated quartz boat is then dried.
[0093] Step 2: Check the airtightness of the furnace tubes; Step 3: Load the wafers and place them in the boat. Heat the furnace tube and keep it at 687°C for 634 seconds. At the same time, purge with nitrogen gas for 3 minutes. Step 4: Evacuate the vacuum for 2 minutes until the pressure is low and the temperature is kept constant at 564℃. Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 577℃; Step 6: First, introduce silane at a high temperature of 545℃, with a silane flow rate of 330 sccm and a time of 56 min; then, introduce silane at a high temperature of 570℃, with a silane flow rate of 270 sccm and a time of 33 min; finally, introduce silane at a high temperature of 550℃, with a silane flow rate of 550 sccm and a time of 36 min.
[0094] After steps 7 and 6 are completed, a vacuum is drawn. The vacuum conditions are set at a temperature of 580℃ for 1 to 3 minutes. Step 8: Back pressure. The back pressure conditions are set as follows: temperature 580℃, nitrogen flow rate 20000 sccm, and time 2.5 min.
[0095] Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
[0096] Example 4 Step 1: Pre-treat the quartz boat by using an alkaline solution to wash it. First, soak the quartz boat in the alkaline solution and then ultrasonically rinse it. The temperature for static soaking is 28℃, and the soaking time is 40 minutes. The ultrasonic rinsing temperature was 36℃, the ultrasonic rinsing frequency was 37kHz, and the ultrasonic rinsing time was 55min.
[0097] The alkaline solution contains 3% NaOH by volume and 3.6% H2O2 by volume in the mixed solution.
[0098] The quartz boat after alkali washing is then washed with water. First, the quartz boat after alkali washing is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 10℃, and the soaking time is 20 minutes; The temperature of the spray rinsing is 10℃, and the flow rate of the spray rinsing is 5m³ / h. 3 / h, the spray rinsing time is 30min.
[0099] The quartz boat was acid-washed using a mixed acid solution. First, the quartz boat was soaked in the mixed acid solution and then ultrasonically rinsed. The temperature for standing soaking is 15℃, and the soaking time is 30 minutes; The ultrasonic rinsing temperature was 30℃, the ultrasonic rinsing frequency was 30kHz, and the ultrasonic rinsing time was 45min.
[0100] The mixed acid solution contains, by mass percentage, 1.1% hydrogen chloride, 0.14% hydrogen fluoride, 0.09% oxidant, 0.08% complexing agent, and 0.03% surfactant, with the balance being water. The oxidant is ammonium persulfate; the complexing agent is a combination of ethylenediaminetetraacetic acid, hydroxyethyliminodiacetic acid, and hydroxyethylethylenediaminetriacetic acid; and the surfactant is a combination of palmitoleic acid and polyethylene glycol.
[0101] The quartz boat after acid pickling is washed with water. First, the acid-pickled quartz boat is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 12℃, and the soaking time is 25 minutes; The temperature of the spray rinsing is 15℃, and the flow rate of the spray rinsing is 12m³ / h. 3 / h, the spray rinsing time is 30min.
[0102] The quartz boat, after being washed, is slowly lifted and dehydrated. The dehydrated quartz boat is then dried.
[0103] Step 2: Check the airtightness of the furnace tubes; Step 3: Load the wafers and place them in the boat. Heat the furnace tube and keep it at 640°C for 590 seconds. At the same time, purge with nitrogen gas for 4 minutes. Step 4: Evacuate the vacuum for 3 minutes until the pressure is low, and keep the temperature constant at 590℃. Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 570℃; Step 6: First, introduce silane at a high temperature of 660℃, with a silane flow rate of 600 sccm and a time of 50 min; then, introduce silane at a high temperature of 620℃, with a silane flow rate of 630 sccm and a time of 35 min; finally, introduce silane at a high temperature of 600℃, with a silane flow rate of 450 sccm and a time of 38 min.
[0104] After steps 7 and 6 are completed, a vacuum is drawn. The vacuum conditions are set at a temperature of 580℃ for 2.5 minutes. Step 8: Back pressure. The back pressure conditions are set at a temperature of 575℃, a nitrogen flow rate of 25000 sccm, and a time of 2 minutes.
[0105] Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
[0106] Example 5 Step 1: Pre-treat the quartz boat by using an alkaline solution to wash it. First, soak the quartz boat in the alkaline solution and then ultrasonically rinse it. The temperature for standing soaking is 30℃, and the soaking time is 35 minutes. The ultrasonic rinsing temperature was 35℃, the ultrasonic rinsing frequency was 35kHz, and the ultrasonic rinsing time was 50min.
[0107] The alkaline solution contains 3.2% NaOH and 4.0% H2O2 by volume in the mixed solution.
[0108] The quartz boat after alkali washing is then washed with water. First, the quartz boat after alkali washing is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 16℃, and the soaking time is 22 minutes; The temperature of the spray rinsing is 12℃, and the flow rate of the spray rinsing is 14m³ / h. 3 / h, the spray rinsing time is 44min.
[0109] The quartz boat was acid-washed using a mixed acid solution. First, the quartz boat was soaked in the mixed acid solution and then ultrasonically rinsed. The temperature for static soaking is 28℃, and the soaking time is 38 minutes; The ultrasonic rinsing temperature was 34℃, the ultrasonic rinsing frequency was 36kHz, and the ultrasonic rinsing time was 51min.
[0110] The mixed acid solution contains, by mass percentage, 1.5% hydrogen chloride, 0.2% hydrogen fluoride, 0.4% oxidant, 0.1% complexing agent, and 0.02% surfactant, with the balance being water. The oxidant is a combination of hydrogen peroxide, peracetic acid, and ammonium persulfate; the complexing agent is a combination of hydroxyethylimine diacetic acid and hydroxyethylethylenediamine triacetic acid; and the surfactant is palmitoleic acid.
[0111] The quartz boat after acid pickling is washed with water. First, the acid-pickled quartz boat is soaked in pure water and then rinsed by spraying. The temperature for static soaking is 14℃, and the soaking time is 30 minutes. The temperature of the spray rinsing is 18℃, and the flow rate of the spray rinsing is 10m³ / h. 3 / h, the spray rinsing time is 40min.
[0112] The quartz boat, after being washed, is slowly lifted and dehydrated; The dehydrated quartz boat is then dried.
[0113] Step 2: Check the airtightness of the furnace tubes; Step 3: Load the wafers and place them in the boat. Heat the furnace tube and keep it at 700℃ for 700 seconds. At the same time, purge with nitrogen gas for 5 minutes. Step 4: Evacuate the vacuum for 3 minutes until the pressure is low, and keep the temperature constant at 600℃. Step 5: Constant pressure ventilation, the furnace tube pressure rises and remains constant at 600℃; Step 6: First, introduce silane at a high temperature of 650℃, with a silane flow rate of 650 sccm and a time of 60 min; then, introduce silane at a high temperature of 500~650℃, with a silane flow rate of 650 sccm and a time of 45 min; finally, introduce silane at a high temperature of 650℃, with a silane flow rate of 650 sccm and a time of 40 min.
[0114] After steps 7 and 6 are completed, a vacuum is drawn. The vacuum conditions are set at a temperature of 600℃ for 3 minutes. Step 8: Back pressure. The back pressure conditions are set as follows: temperature 600℃, nitrogen flow rate 30000 sccm, and time 3 min.
[0115] Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
[0116] Table 2 Performance parameter data for Examples 1-5 The second set of experiments analyzed the performance parameters of the battery cells produced by the two processes. The cleaned carrier was the control group, and the uncleaned carrier was the experimental group. As shown in Table 2, the results show that the yield of the experimental group was slightly improved compared with the control group. However, in the field of industrial manufacturing, even a small efficiency improvement can bring huge economic benefits.
[0117] The improved film thickness enhanced the quality of the passivation layer, effectively reducing surface recombination and improving the passivation effect of the cell. Optimized passivation and doping resulted in a slight increase in the Voc (open-circuit voltage) of the photovoltaic cell, thereby increasing its output power.
[0118] In summary, the application of non-washable substrates in TOPCon process technology significantly improves photovoltaic cell performance by enhancing film thickness uniformity, optimizing passivation and doping effects, and increasing Voc and FF. This technology injects new vitality into the photovoltaic industry and provides strong support for the research and development of more efficient and environmentally friendly photovoltaic cells in the future.
[0119] The present invention has been further described above with reference to specific embodiments. However, it should be understood that the specific description herein should not be construed as limiting the nature and scope of the present invention. Various modifications made to the above embodiments by those skilled in the art after reading this specification are all within the scope of protection of the present invention.
Claims
1. A method for improving the thickness of polycrystalline silicon films between poly wafers in TOPCon solar cells, characterized in that, The production of polycrystalline silicon films using the LPCVD double-intercalation process includes the following steps: Step 1: Pre-treat the quartz boat, excluding the quartz boat holder, to reduce silane consumption when only the quartz boat is washed and not the boat holder. The pre-treatment includes the following steps: alkaline washing of the quartz boat with an alkaline solution; water washing of the alkaline-washed quartz boat; acid washing of the quartz boat with a mixed acid solution; water washing of the acid-washed quartz boat; slow lifting and dehydration of the water-washed quartz boat; and drying of the dehydrated quartz boat. Step 2: Check the airtightness of the furnace tubes; Step 3: Wafer loading and boat loading. Load the silicon wafers into the quartz boat, transport the quartz boat into the furnace tube, heat the furnace tube and keep it at 600~700℃ for 500~700s, while purging with nitrogen gas for 3~5min. Step 4: Evacuate the furnace tube after the treatment in Step 3 for 2-3 minutes until the pressure is low, and keep the temperature constant at 550-600℃. Step 5: Constant pressure ventilation. A certain amount of silane is pre-introduced into the furnace tube after the treatment in Step 4 to make the furnace tube pressure rise and maintain constant pressure. The constant pressure is maintained at 150 mbar and the temperature is kept constant at 550~600℃. Step 6: Multilayer deposition process. First, silane is introduced at high temperature, causing it to thermally decompose into a first layer of elemental silicon, which is deposited on the passivation layer surface. Second, silane is introduced at high temperature, causing it to thermally decompose into a second layer of elemental silicon, which is deposited on the passivation layer surface. Third, silane is introduced at high temperature, causing it to thermally decompose into a third layer of elemental silicon, which is deposited on the passivation layer surface. The parameters for the first deposition are set as follows: temperature 500-650℃, silane flow rate 200-650 sccm, time 45-60 min; for the second deposition, temperature 500-650℃, silane flow rate 200-650 sccm, time 30-45 min; for the third deposition, temperature 500-650℃, silane flow rate 200-650 sccm, time 35-40 min. Step 7: After the multilayer deposition process is completed, the unreacted gas and some products are extracted from the furnace tube by a vacuum pump. The vacuum conditions are set at a temperature of 550~600℃ and a time of 1~3min. Step 8: Back pressure, nitrogen gas is introduced into the furnace tube to bring the pressure back to atmospheric pressure, in preparation for unloading the boat; Step 9: Unload the silicon wafer from the quartz boat, insert it into the basket, and transfer it to the next process.
2. The method for improving the thickness of the polycrystalline silicon film between poly wafers in a TOPCon solar cell according to claim 1, characterized in that, The alkaline solution is a mixture of NaOH and H2O2, wherein NaOH accounts for 2.5-4.0% of the volume fraction of the mixture and H2O2 accounts for 3.5-6.0% of the volume fraction of the mixture.
3. The method for improving the thickness of the polycrystalline silicon film between poly wafers in a TOPCon solar cell according to claim 2, characterized in that, The mixed acid solution comprises the following components by mass percentage: 0.3-1.5% hydrogen chloride, 0.1-0.2% hydrogen fluoride, 0.05-0.4% oxidant, 0.05-0.1% complexing agent, 0.02-0.05% surfactant, and the balance being water.
4. The method for improving the thickness of the polycrystalline silicon film between poly wafers in a TOPCon solar cell according to claim 3, characterized in that, The oxidant is selected from any one or a combination of at least two of hydrogen peroxide, peracetic acid, or ammonium persulfate; The complexing agent is any one or a combination of at least two of ethylenediaminetetraacetic acid, hydroxyethyliminodiacetic acid, and hydroxyethylethylenediaminetriacetic acid; The surfactant is any one or a combination of at least two of palmitic acid, polyethylene glycol, or fatty alcohol polyoxyethylene ether.
5. The method for improving the thickness of the polycrystalline silicon film between poly wafers in TOPCon solar cells according to any one of claims 1 to 4, characterized in that, The alkaline washing treatment is carried out according to the following steps: First, the quartz boat is immersed in the alkaline solution and then ultrasonically rinsed. The temperature for static soaking is 15-35℃, and the soaking time is 30-50 minutes; The ultrasonic rinsing temperature is 30-40℃, the ultrasonic rinsing frequency is 30-40kHz, and the ultrasonic rinsing time is 45-60min. The pickling process is carried out according to the following steps: First, the quartz boat is immersed in the mixed acid solution and then ultrasonically rinsed. The temperature for static soaking is 15-35℃, and the soaking time is 30-50 minutes; The ultrasonic rinsing temperature is 30-40℃, the ultrasonic rinsing frequency is 30-40kHz, and the ultrasonic rinsing time is 45-60min. The specific steps of the water washing treatment are as follows: First, soak the quartz boat that has been acid-washed or alkali-washed in pure water, and then rinse it with spray. The temperature for static soaking is 10-20℃, and the soaking time is 20-40 minutes; The temperature of the spray rinsing is 10–20℃, and the flow rate is 5–15 m³ / h. 3 / h, the spray rinsing time is 30-60min.
6. The method for improving the thickness of the polycrystalline silicon film between poly wafers in a TOPCon solar cell according to claim 1, characterized in that, The back pressure conditions in step 8 are set as follows: temperature 550~600℃, nitrogen flow rate 10000~30000sccm, and time 1~3min.
Citation Information
Patent Citations
Method for improving uniformity of high-temperature oxide layers of wafers
CN101906617A
Wafer boat assembly and semiconductor process equipment
CN116240527A